A Near-Rational Model of the Business Cycle, with Wage and Price Inertia - Akerlof, G. A.; Yellen, J. L. (Quarterly Journal of Economics, 1985)
This paper presents a model in which insignificantly suboptimal behavior causes aggregate demand shocks to have significant real effects. The individual loss to agents with inertial price-wage behavior is second-order in terms of the parameter describing the shock, while the effect on real economic variables is first-order. Thus, significant changes in business activity can be generated by anticipated money supply changes provided that some agents are willing to engage in nonmaximizing behavior which results in small losses.